Effects of reduced cost-sharing on children's health: Evidence from Japan. (February 2016) - Takaku, Reo
Abstract: Although childhood health status is widely recognized as an important determinant for future achievement and health, there are few studies on the impact of patient cost-sharing on children's health. This paper investigates whether reduced cost-sharing leads to an improvement of health status among preschool and school-age children in Japan, exploiting regional disparities in expansions of municipality-level subsidy programs for out-of-pocket expenditure. With the eligibility for this subsidy program, known as the Medical Subsidy for Children and Infants (MSCI), the coinsurance rate generally decreases from 30% or 20% to zero for outpatient health care services and drug prescriptions. In order to uncover the impact of this program, I conducted an original survey of all municipalities in Japan to understand the time-series evolution of the eligible age for the MSCI in October 2013 (weighted response rate = 75%), and the probability of being eligible for the MSCI was then calculated by the age, prefecture of residence, and year. These probabilities were matched to children's health data from the Comprehensive Survey of Living Conditions from 1995 to 2010. The results show that eligibility for the MSCI improves subjective measures of health status among preschool children (n = 115, 019). However, I find no such improvement among school-age children (n = 133, 855). In addition, MSCI eligibility does not reduce hospitalization among either preschool or school-age children. Taken together, this study finds no discernible effects on health among school-age children, suggesting recent rapid expansions of the MSCI for this age group have not been associated with the improvement of health status. Highlights: Impacts of patient cost sharing on health outcomes are still uncertain. I investigate whether reduced cost-sharing improves children's health in Japan. Dramatic expansions of the medical subsidy program for children are exploited. The subsidy program does not reduce hospitalization among preschool and school-age children.